Diagnosis of vertebral mineral metabolism disorders in patients with drug-resistant pulmonary tuberculosis using computed tomography data - М.І. Lynnyk; V.І. Іgnatieva; G.L. Gumeniuk; V.А. Svyatnenko; N.M. Bobok (Infusion & Chemotherapy)
BACKGROUND. In patients with widespread pulmonary tuberculosis, the disease with pronounced symptoms of intoxication may be due to the disruption of protein metabolism and the function of the hepatobiliary system, and thus, a decrease in the level of amino acids in the liver, protein, substituted for ammonia, indicators of ALT, AST, thymol test. Changing biochemical test results to confirm the presence of hepatotoxic, cholestatic or mixed side effects of antimycobacterial drugs. Their influx into the development of osteoporosis without surviving, behind the blame of lonely work twenty years ago. In connection with this, diagnosis and treatment of the dynamics of disruption of mineral metabolism of bone tissue in patients with drugresistant tuberculosis based on computed tomography (CT) data of the chest organs are relevant.